(untitled) (Revista Contexto & Saúde, 2026)
Objective: to analyze the experiences that motivated women to choose planned home birth after vaginal hospital birth. Method: this is a qualitative, descriptive and exploratory study carried out in western Santa Catarina, southern Brazil, with women who had planned home births after previous vaginal hospital births. Data were collected from September to December 2022, in a triangulated manner, through semi-structured interviews, information collected from pregnant women’s notebooks and from the registration forms of the teams that attended the births. Thematic content analysis was used, culminating in the theme “Previous hospital experiences”. Results: Eleven women participated in the study and reported previous negative hospital experiences, including various forms of obstetric and neonatal violence as the main motivations for choosing home birth. The reports revealed trauma and dissatisfaction with hospital care, highlighting unnecessary interventions, lack of privacy and disrespect for personal preferences during the parturition period and postpartum, which led women to desire a more respectful and personalized environment in subsequent pregnancies. Conclusion: the choice of planned home birth reflects women’s search for greater autonomy and safety in the birth process, with care that values ​​respect and focuses on the quality of care provided to the mother and baby. There is a need to review hospital practices and promote humanized care that values ​​the protagonism and physiology of the parturient woman.